Global distribution of fin whales Balaenoptera physalus in the post‐whaling era (1980–2012). (October 2015) - Edwards, Elizabeth F.; Hall, Candice; Moore, Thomas J.; Sheredy, Corey; Redfern, Jessica V.
Abstract The global distribution of fin whales Balaenoptera physalus is not fully understood. Existing maps can be divided into two conflicting categories: one showing a continuous global distribution and another showing an equatorial hiatus (gap in the global distribution) between approximately 20°N and 20°S. Questions also remain about the seasonal distribution of fin whales. To explore the suggested equatorial hiatus and seasonal distribution patterns, we synthesised information on fin whale distribution in the post‐whaling era (1980–2012) from published literature, publicly available reports and studies conducted by various organisations. We created four seasonally stratified maps showing line‐transect density estimates, line‐transect survey effort, acoustic detections, and sightings. An equatorial hiatus in the global distribution of fin whales during the post‐whaling era is supported by numerous line‐transect surveys and by the rarity of equatorial acoustic detections and sightings, and corroborated by whaling era reports, morphological analyses, and genetic analyses. Our synthesis of post‐whaling era data is consistent with results from other studies indicating that fin whales are more abundant at higher latitudes during warmer months and more abundant at lower latitudes (although these latitudes are still greater than 20°) during colder months. However, our synthesis and results from other studies also indicate that some fin whales in both hemispheres remain in higher latitudes (50°–60° north or south) during colder months and in lower latitudes (to approximately 20°–30° north or south) during warmer months, indicating that seasonal fin whale movements differ from the seasonal migrations of blue whales Balaenoptera musculus and humpback whales Megaptera novaeangliae. Our maps of global fin whale distribution provide a comprehensive picture of current knowledge and highlight important geographical and temporal data gaps. Surveys should be conducted within the identified data gaps in order to increase fine‐scale spatial and temporal knowledge of distribution patterns, improve fin whale taxonomy, and identify areas of elevated fin whale densities that may require management of threats, such as ship strikes.